A study of inhibition and reversal of plasmodium Falciparum cytoadherence using rna apatamer specific to icam-1 /cd54 and cd36 protein - Khairul Mohd, Fadzli Mustaffa (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2018)
Malaria is a life-threatening disease caused by parasites transmitted to humans through the bite of infected Anopheles mosquitoes. The disease mostly affects children, pregnant women, non-immune persons, and individuals with chronic diseases such as human immunodeficiency virus and acquired immunodeficiency syndrome (HIV I AIDS). Malaria causes complications such as severe anemia, metabolic acidosis, and cerebral malaria, often leading to death if not treated within 24 h [1,2]. The World Health Organization (WHO) reported there were 438,000 deaths caused by malaria worldwide, especially in the endemic areas such as Africa [3]. In humans, malaria is caused by five distinct Plasmodium species, namely P falciparum, P vivax, P malariae, P knowlesi, and two sub-species of Plasmodium ovale (Po. curtisi and Po. wallikeri) [4-6]. Of these, P falciparum causes the most severe disease due to higher parasitemia, and it is responsible for the massive burden of global mortality and morbidity [7,8]. Despite extensive interventions by WHO to prevent, control and eliminate malaria, the transmission of the disease continues in many countries around the world. The interventions consist of an array of drugs, insecticides, diagnostics, and understanding of the breeding site criteria [9]. Other factors that contribute to the prevalence of malaria include increased transmission risks among people who are non-immune to the disease~ the growth in international travel and migration, and the escalation of drug-resistant parasites [10]. However, the underlying mechanism that contributes to malaria severity in a patient is still not well understood, adding to the difficulty in curbing the disease's progression. Several drugs are available for malaria treatment including chloroquine, sulfadoxine/pyrimethamine (SP), and quinine, which are working well in many parts of the world. Unfortunately, there is a grave concern that the malaria parasites have developed a widespread resistance to anti-malarial drugs, especially in the endemic regions [11,12]. Anti-malarial drug resistance has been observed for P. falciparum, P. vivax and P. malariae in most parts of the world [13]. The SP resistance is seen in Papua New Guinea, Thailand, Indonesia, Madagascar, Iran, Afghanistan, India, and Pakistan